Na straży zasad dziennikarstwa okresu międzywojennego - Hrycek, Miłosz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
The regaining of independence enabled the development of press publishing and social and political life. The Polish press quickly made up for losses incurred during the period of Partition. However, the rapid growth and commercialization of the publishing market did not necessarily reveal only positive aspects. The development of the tabloid press, whose purpose was to provide information in a highly attractive manner to the reader, did not help maintain a high level of competence. Apart from this, one widely discussed problem affecting opinion journalism, a problem also connected with the formation of the profession, was the “journalist’s ethos”. The importance of this problem is best reflected in attempts by journalists and persons linked to journalism to strengthen the ethical aspect of the profession, and in discussions concerning journalists’ ethics of that time.